Evaluation of the dynamic response of structures using auxetic-type base isolation (Fracture and Structural Integrity, 2019)
Base isolation is a widely-used method used to minimise the harmful effects of earthquakes on buildings. Unlike a fixed base building, a building with a base isolation system essentially decouples the superstructure from the substructure resting on the ground. Then, during earthquakes, the superstructure’s relative displacement is significantly reduced, minimising the structural damage. Auxetics, which are materials with a negative Poisson’s ratio, are known for possessing properties such as high energy absorption. Based on the energy absorbing capabilities of auxetic materials, it is proposed that incorporating them into base isolation structures would positively impact on the performance of the system. Therefore, the article aims to investigate the response of structures under seismic loading incorporating re-entrant hexagon layers into the base isolation system. This is assessed by defining and numerically testing the system using finite element analysis. The models developed for this study represent multi-storey structural steel frames combined with fixed base, conventional lead-rubber bearing and auxetic composite base isolation. Differences in the response obtained from the mentioned systems are highlighted. Results indicate that the auxetic base isolation may improve the dynamic response of structures, although a unique performance is not recorded.
Keywords: Auxetic Materials; Seismic Actions; Base Isolation; Finite element analysis; Structural Damage